Orbital angular momentum-resolved convergent-beam electron diffraction by the post-selected injection of electron beam. (14th September 2022) - Saitoh, Koh; Yonezawa, Tatsuya; Nambu, Hiroki; Tanimura, Shogo; Uchida, Masaya
Abstract: Recent advances in the production of electron vortex beams carrying orbital angular momentum (OAM) offer unique opportunities to explore materials at the nanoscale level. We present a novel method for observing convergent-beam electron diffraction (CBED) patterns by using an electron vortex beam. In a transmission electron microscope, a series of electron vortex beams generated by a forked grating mask located above the specimen illuminate the specimen, and CBED patterns are imaged onto the observation plane of the microscope, selecting one of the electron vortex beams using an aperture located beneath the specimen. We demonstrate that the post-selection method yields the same OAM-resolved CBED patterns as when a single convergent electron beam is injected. The formation mechanism of the post-selected CBED is also discussed. This post-selection method is general and can be applied to electron energy-loss spectroscopy to probe multipole excitations using electron vortex beams.